1979
DOI: 10.1161/01.str.10.3.238
|View full text |Cite
|
Sign up to set email alerts
|

The carotid bifurcation plaque: pathologic findings associated with cerebral ischemia.

Abstract: SUMMARY Embolization from or decreased flow through cervical carotid and vertebral arteries causes ischemic stroke syndromes. Specific pathologic findings were studied in SO symptomatic patients who underwent 69 carotid endarterectomies. Detailed analyses of their carotid plaques included correlations between photographs of gross specimens, microscopic findings, angiograms, preoperative symptoms and long-term postoperative follow up. Carotid plaques were primarily fibrous with significant (> 70%) stenoses enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0
5

Year Published

1981
1981
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(83 citation statements)
references
References 20 publications
2
76
0
5
Order By: Relevance
“…2- 4 The importance of PH was suggested by Imparato et al, who reported, in 1979, that PH was responsible for 73% of focal neurological symptoms in patients with symptomatic carotid artery disease and that it played a significant role in plaque progression. 5 Similar results have been reported by Takaya et al in a longitudinal magnetic resonance imaging (MRI) study. 6 A recent systematic review (of 31 observational studies) also suggested a plausible contribution of PH to focal neurological symptom production.…”
supporting
confidence: 82%
“…2- 4 The importance of PH was suggested by Imparato et al, who reported, in 1979, that PH was responsible for 73% of focal neurological symptoms in patients with symptomatic carotid artery disease and that it played a significant role in plaque progression. 5 Similar results have been reported by Takaya et al in a longitudinal magnetic resonance imaging (MRI) study. 6 A recent systematic review (of 31 observational studies) also suggested a plausible contribution of PH to focal neurological symptom production.…”
supporting
confidence: 82%
“…While carotid IMT and stenosis have been demonstrated to have strong associations with clinically-evident stroke, 10,14,15 CT-defined infarcts, 16,17 and more recently with MRI-defined infarcts, 18,19 less information is available on relationships of atherosclerosis severity to other MRI abnormalities such as 3 and between ventricular and sulcal enlargement and severity of carotid atherosclerosis. 2 Given the strong and consistent relationships of MRI abnormalities to severity of carotid atherosclerosis, the question arises whether there are other ultrasound-definable characteristics of carotid disease that are related to MRI abnormalities.…”
Section: Carotid Disease and The Brainmentioning
confidence: 99%
“…Clinical studies of carotid atherectomy specimens suggest that ulcerated, 20 less organized, 15 and hemorrhagic 21,22 plaques are associated with symptoms. Some of these associations have been disputed, however, with other investigators failing to demonstrate more frequent symptoms associated with ulcerations 14,21 and plaque hemorrhage. 23,24 The documented ability of B-mode ultrasonographic scanning to detect plaque ulceration, 25 heterogeneity, 26,27 and hemorrhage, 28 though disputed by some, 24,29,30 has led to the demonstration that these ultrasound-defined characteristics are also associated with ipsilateral neurologic symptoms, 31 clinical events, 26 and MRI-defined infarcts.…”
Section: Carotid Disease and The Brainmentioning
confidence: 99%
“…The association between the presence of carotid intraplaque hemorrhage and neurologic events was first described in endarterectomy specimens. 17 In 1996, Toussaint et al showed that in T2W sequences the atheromatous core has low signal intensity relative to the fibrous cap and outer layers of the vessel wall, and that areas of the plaque containing calcified tissue exhibit very low signal intensity because of their low water proton content. 18 Plaque lipids consist primarily of unesterified cholesterol and cholesterol esters, which are associated with a short T2.…”
Section: Assessment Of Atherosclerotic Carotid Artery Plaquesmentioning
confidence: 99%